Hubungan Pekebun dan Tauke Kelapa Sawit di Desa Puo Raya Kecamatan Tandun Kabupaten Rokan Hulu - Teresia, Yossi; Restuhadi, Fajar; Andriani, Yulia (JALOW | Journal of Agribusiness and Local Wisdom, 2023)
This study aims to find out the relationship between smallholders and tauke. The data analysis methods employed were descriptive analysis, Cartesian diagram analysis, and the Fishbein multi-attribute attitude model. The research findings indicate that for the sale of oil palm, farmers utilize the services provided by the oil palm patron. The characteristics of oil palm farmers in Puo Raya Village show that on average, they are aged between 31-40, have an average education level of junior high school and high school, have 4-10 years of experience in oil palm cultivation, have 2-3 dependents, produce 4300-7500 kg permonth, and have an average income of Rp 9,300,000-14,500,000 with average expenses of Rp 5,300,000-8,500,000. The characteristics of the oil palm patron in Puo Raya Village show that on average, they are aged between 31-40, have an equivalent education level of high school, have 10-15 years of farming experience, have 0-1 or 4-5 dependents, produce more than 8000 kg per month, and have an average income of more than Rp 15,000,000 permonth with average expenses of Rp 6,100,000-9,000,000 per month. The dominant method of selling oil palm by farmers is through the transportation services provided by the patron. Attributes such as fast and good service, upfront payment, provision of holiday allowances (THR), loan provision, and cash payment are considered advantages and should be maintained by the patron. The attitude of farmers towards the patron is categorized as good. The patron-client relationship pattern in Puo Raya Village is not only economic but also non-economic.